1998
DOI: 10.1159/000014004
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of Urea Synthesis Capacity in Preterm Infants with Intrauterine Growth Retardation

Abstract: The postnatal development of the urea-synthesizing capacity was studied in 21 preterm infants with intrauterine growth retardation (IUGR) and compared with results found in 12 infants without IUGR as controls. The urea-synthesizing capacity was estimated by the ratio Q of 15N abundance of ammonia and urea in 6-hour urine samples collected after enteral administration of 3 mg [15N]H4Cl/kg body weight. The measurements were performed on the first day when a protein intake of 3.0–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
2
6
0
1
Order By: Relevance
“…Preterm SGA infants have higher metabolic rates and increased energy expenditure when compared to AGA infants in the first month of life (Bohler et al, 1999, Chessex et al, 1984, Davies et al, 1996). Some studies show that SGA infants are more efficient at protein gain (Cauderay et al, 1988, Van Goudoever et al, 1995), and others indicate that SGA infants have deficiencies in protein metabolism (Boehm et al, 1988, Boehm et al, 1998). We do not have a clear understanding of how to best provide nutrition to the IUGR neonate, especially when they are born preterm and require supplemental nutrition either by enteral or parenteral nutrition.…”
Section: Potential Strategies To Improve Muscle Growthmentioning
confidence: 99%
“…Preterm SGA infants have higher metabolic rates and increased energy expenditure when compared to AGA infants in the first month of life (Bohler et al, 1999, Chessex et al, 1984, Davies et al, 1996). Some studies show that SGA infants are more efficient at protein gain (Cauderay et al, 1988, Van Goudoever et al, 1995), and others indicate that SGA infants have deficiencies in protein metabolism (Boehm et al, 1988, Boehm et al, 1998). We do not have a clear understanding of how to best provide nutrition to the IUGR neonate, especially when they are born preterm and require supplemental nutrition either by enteral or parenteral nutrition.…”
Section: Potential Strategies To Improve Muscle Growthmentioning
confidence: 99%
“…Thus, early studies suggested BUN is not a valid measure of protein intake in preterm infants. 4,[9][10][11] More recent studies, one by this group, 12 suggest otherwise in the clinically stable preterm infant. 13 In the latter study, the relationship between nitrogen accretion and growth fed two levels of protein intake, 3.0 and 3.6 g/100 kcal, was assessed.…”
mentioning
confidence: 99%
“…Recently, a direct relation between birth weight and number of glomeruli in humans has been suggested in a morphological study [7], however, birth weight/length ratio may be a more sensitive measure of IUGR [8]. Other groups have also found evidence of impaired renal function in newborn suffering from IUGR [3, 4]. Brenner and Chertow [9] originally suggested that reduced glomerular filtration capacity, as seen in individuals born with fewer functioning nephrons, predicts susceptibility to systemic and glomerular hypertension and kidney disease later in life [13].…”
Section: Discussionmentioning
confidence: 99%
“…[1]. Intrauterine growth retardation (IUGR) may lead to congenital retardation of renal development [2–4] and a reduction in nephron number [2, 5, 6]. One clinical expression of IUGR is low weight at birth, and this has recently been associated with reduced number of glomeruli in humans [7].…”
Section: Introductionmentioning
confidence: 99%